CONTRIBUTION OF THE KASHKADARYA REGIONAL MUSICAL DRAMA THEATER TO THE RISE OF THE CULTURAL AND SPIRITUAL LIFE OF THE POPULATION (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the analysis of the activities and activities of musical drama theaters in Kashkadarya region during the years of independence.